Diet Quality Indices and Leukocyte Telomere Length Among Healthy US Adults: Data From the National Health and Nutrition Examination Survey, 1999–2002 - Leung, Cindy W (Am J Epidemiol, 2018)
Aging is the biggest risk factor for the development of chronic diseases. Telomere length may represent one important mechanism by which dietary intake influences risk of age-related diseases; however, it is unknown which diet pattern is most strongly related to telomere length. We compared the relationships between 4 evidence-based diet quality indices and leukocyte telomere length in a nationally representative sample of healthy adults, and the extent to which these associations differed between men and women. Data on 4,758 adults aged 20–65 years with no prior diagnosis of major chronic disease were obtained from the 1999–2002 cycles of the National Health and Nutrition Examination Survey. Diet was assessed using one 24-hour dietary recall. After adjustment for sociodemographic and health characteristics, comparison of the top and bottom quintiles showed that higher Healthy Eating Index 2010 scores (β = 0.065, 95% confidence interval (CI): 0.018, 0.112; P-trend = 0.007), Alternate Healthy Eating Index 2010 scores (β = 0.054, 95% CI: 0.010, 0.097; P-trend = 0.007), Mediterranean Diet scores (β = 0.058, 95% CI: 0.017, 0.098; P-trend = 0.008), and Dietary Approaches to Stop Hypertension (DASH) scores (β = 0.052, 95% CI: 0.014, 0.090; P-trend = 0.007) were each associated with longer telomere length in women. These results may provide insight into the complex associations between optimal nutrition and longevity. Further investigation is needed to understand why associations were not observed in men.